APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES DURING INDUSTRIAL EDUCATION AS A MEANS OF MOTIVATION AND ACTIVATION OF STUDENTS' COGNITIVE ACTIVITY (Innovative professional education, 2024)
The article examines the issue of modern approaches in the educational environment of the master of industrial training, namely: the use of information and communication technologies in the conduct of in-service lessons in the conditions of distance learning.
Keywords: nformation and communication technologies, distance learning, interactive exercises, educational process